Development of a WebGIS-Based System for Mapping Priority Investment Areas in MSME Development at DPMPTSP Asahan Regency - Pradipa, Naila Hanni; Sembiring, Muhammad Ardiansyah; Rohminatin, Rohminatin (SAINTIS Publishing, 2025)
Regional development is greatly aided by investment, especially when it comes to Micro, Small, and Medium-Sized Enterprises (MSMEs). At DPMPTSP Asahan, investment data has traditionally been managed using static spreadsheets, making it difficult for new investors to understand regional potential, especially when they are unfamiliar with the area. This study employs a qualitative approach through observation, interviews, and document analysis. The resulting system uses OSS-RBA data with interactive maps and filtering tools that enable users to explore MSME distributions by sector and location. Developed using PHP, CodeIgniter, and Leaflet.js, the WebGIS system facilitates intuitive access to business legality information, administrative boundaries, and geospatial insights. The system improves communication between DPMPTSP officers and investors by allowing spatial-based explanations that replace conventional tabular presentations. Investors can better grasp economic zones, accessibility, and sectoral opportunities through map-based exploration. These features are especially useful in early investment decision-making stages. Unlike prior systems that lack interactivity and licensing data integration, this system bridges that gap with investor-friendly features and a modular architecture. The WebGIS platform enhances service delivery, increases transparency, and supports data-driven policymaking in investment promotion. It serves as a scalable model for other regional governments seeking to digitize and spatially enhance investment-related information systems.